From acceptera to Vällingby: The Discourse on Individuality and Community in Sweden (1931-54) - Lucy Creagh (Footprint)
The Swedish suburb of Vällingby, completed in 1954, culminated an investigation into the housing problem which can be traced back to the functionalist manifesto acceptera of 1931, where the issue of finding a ‘Middle Way’ between the individual and the mass, the personal and the universal was presented as being as central to the project of modern architecture as it was to Social Democracy as a whole.